Linux administrator street smarts : - Smith, Roderick W. (John Wiley, 2007)
Hit the ground running with the street-smart training you'll find in this practical book. Using a "year in the life" approach, it gives you an inside look at Linux administration, with key information organized around the actual day-to-day tasks, scenarios, and challenges you'll face in the field. This valuable training tool is loaded with hands-on, step-by-step exercises covering all phases of Linux administration